Performance of two aromatic grasses grown in association with mulberry trees on degraded land in the north-western Himalayan foothills. Issue 1 (2nd January 2023) - Tomar, J.M.S.; Kumar, Pawan; Gupta, A.K.; Kaushal, R.; Mehta, H.
ABSTRACT: The study investigated the potential of aromatic-grass-based agroforestry systems to rehabilitate degraded land in the north-western Himalayas. Five treatments; sole lemon grass ( Cymbopogon flexuosus ) (LG), sole java grass sole ( Cymbopogon winterianus ) (JG), lemon grass + Morus alba (LG + M), java grass + M. alba (JG + M) and sole M. alba (M) were planted in a randomised block design and the systems were evaluated in terms of plant and tree growth and yields over three years and effects on soil quality characteristics. Considering the 3-year averages, the highest survival rate of the grass (95%) was recorded in sole lemon grass, while the highest plant height (117 cm), number of tillers clump −1 (67), clump diameter (104 cm), fresh biomass (179 Mg ha −1 ), dry biomass (60 Mg ha −1 ) and oil yield (89 kg ha −1 ) of the grass were recorded for the lemon grass + M. alba treatment. The highest total fresh root weight (128.7 g clump −1 ) and number of total roots (511.7 clump −1 ) were recorded under sole lemon grass and for lateral root spread (78.8 cm) was recorded under sole java grass. The highest soil organic carbon and potassium concentrations were recorded in sole M. alba . The treatment with sole M. alba was recorded to have the highest values for the soil biological properties followed by the treatments with lemon grass.